Coitus and orgasm at term: effect on spontaneous labour and pregnancy outcome - Tan, P.C.; Yow, C.M.; Omar, S.Z. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Women who reported coitus were less likely to go into spontaneous labour prior to their scheduled labour induction. Reported coitus and orgasm were not associated with adverse pregnancy outcome.